A politização do corpo na “marcha das mulheres”: um dispositivo de discurso e de poder - Costa, Hilda Rodrigues da (2019)
This theses aims to describe and analyza, in the light of the theoretical contributions of Discourse Analysis, the articulation of power over the politicization of the female body on the covers of Veja magazine, through the relations of power-knowledge that are realized through devices of security, sexuality and media as effects of truth and resistance, presente in statements of the cover of Veja magazine. When faced with the contexto of some report derived from these statements in the body of the jornal, we feel the need to presente, albeit briefly, certain statements presente within the journals that make up these discursive plots, in order to meet our research objetive analyze the politicization of the female body, describing the articulations between the materiality of utterances, their insertion in discursive formations, their inscription in a historical a priori, their control, their circulation, their rules of appearance and delimitation, through practices recorded by the media. We used as analytical-descriptive Research method, starting from the theoretical assuptions of Michel Foucault as the notions of discourse and utterance, without disregarding the methodological theoretical support of archeology. Veja magazine covers were selected for analysis, from 1968 to 2018,which set out a discursive course, directly or indirectly, about the marcho of women for their rights, which were sometimes silenced or erased from history through institutionalized, manipulated, articulated discourses governing “the will to be a woman”, depriving her of her rights through strategies of a power-knowledge capable of categorizing gender in the body’s production process, through print and digital media. The studies by Inês Araujo, Gilles Deleuze, Michel Foucault, Giorgio Agamben, Margareth Rago, among others, were essential for understanding the processes of subjectivation regarding the strategies and mechanisms of discursive and representational condendation of women which are anchored in the discursive memory of society. Therefore, the marcho f womwn throughout history is a movement of resistance and struggle that seeks the right to reinvente itsself through the narratives of a new history, even with inequalities knocking on the door, trying to naturalize the subordination role of women, disqualifying the feminime act through ideological and hegemonic constructions.